2009
DOI: 10.1128/jb.01720-08
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the DraT/DraG System for Posttranslational Regulation of Nitrogenase in the Endophytic Betaproteobacterium Azoarcus sp. Strain BH72

Abstract: DraT/DraG-mediated posttranslational regulation of the nitrogenase Fe protein by ADP-ribosylation has been described for a few diazotrophic bacteria belonging to the class Alphaproteobacteria. Here we present for the first time the DraT/DraG system of a betaproteobacterium, Azoarcus sp. strain BH72, a diazotrophic grass endophyte. Its genome harbors one draT ortholog and two physically unlinked genes coding for ADP-ribosylhydrolases. Northern blot analysis revealed cotranscription of draT with two genes encodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…In contrast, DraG belongs to the ADP-ribosyl-hydrolase family, and shares a much higher sequence and structural similarity to all members of this family, including orthologues in archaea, bacteria and eukarya (Koch-Nolte et al, 2008). DraG orthologues are widely distributed in prokaryotes, including organisms that do not encode DraT or NifH proteins (Oetjen & Reinhold-Hurek, 2009), suggesting that these orthologues have evolved different functions. The regulation of DraT and DraG activities DraT and DraG activities are subject to opposing regulation in vivo according to the prevailing nitrogen or energy levels (Kanemoto & Ludden, 1984;Liang et al, 1991;Zhang et al, 1993).…”
Section: Distribution Of the Nitrogenase Adp-ribosylation System In Pmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, DraG belongs to the ADP-ribosyl-hydrolase family, and shares a much higher sequence and structural similarity to all members of this family, including orthologues in archaea, bacteria and eukarya (Koch-Nolte et al, 2008). DraG orthologues are widely distributed in prokaryotes, including organisms that do not encode DraT or NifH proteins (Oetjen & Reinhold-Hurek, 2009), suggesting that these orthologues have evolved different functions. The regulation of DraT and DraG activities DraT and DraG activities are subject to opposing regulation in vivo according to the prevailing nitrogen or energy levels (Kanemoto & Ludden, 1984;Liang et al, 1991;Zhang et al, 1993).…”
Section: Distribution Of the Nitrogenase Adp-ribosylation System In Pmentioning
confidence: 99%
“…(Oetjen & Reinhold-Hurek, 2009). The genes usually constitute an operon and are presumably co-transcribed.…”
Section: Distribution Of the Nitrogenase Adp-ribosylation System In Pmentioning
confidence: 99%
See 1 more Smart Citation
“…It is able to express the nif ‐genes in roots of rice [20] and Kallar grass [21], provides fixed nitrogen to its host plant [22], and is thus an interesting candidate for studies of the nitrogenase regulatory mechanism. Phylogenetic analysis indicated that the system for the post‐translational modification of nitrogenase Fe‐protein is probably also present in the δ‐ and γ‐subdivision of the Proteobacteria [17]; however, it has not yet been analyzed in detail outside the α‐subdivision of Proteobacteria .…”
mentioning
confidence: 99%
“…One is the well-defined DraT/DraG system, which is involved in the regulation of nitrogenase activity. In response to a negative stimulus such as the presence of ammonium or a decrease in the available cell energy, DraT can ADP-ribosylate Fe protein which in turn dissociates from MoFe protein and ultimately inhibits the nitrogenase activity, while DraG can remove the ADP-ribose moiety from Fe protein and therefore reactivate the nitrogenase [17,18]. In addition to DraT, some toxins secreted by pathogens also possess ADP-ribosylation activity and can disrupt the essential functions of the host cells [13,16,19].…”
Section: Introductionmentioning
confidence: 99%